Análise das taxas de acidentes de trabalho e fatores de risco associados aos óbitos no Rio Grande do Sul - Fillipin, Gabriela Granzotto (2020)
The occurrence of accidents at work is daily, but a large part of them is not registered for many reasons, causing damage and injury to worker's health and, consequently, it influences the productivity of companies and industries. Accidents and deaths are indicative of working conditions and associated risk factors, and report the precariousness of the inspection system in relation to the health and safety of workers. A systematic literature review was carried out, searching for papers in the Web of Science and Scopus databases and applied as infometric analysis techniques, with the aim of seeking evidence from the state of the art on the relationship between economic activities and work accidents. A study of accident and death rates due to work accidents in the state of Rio Grande do Sul was conducted between 2011 and 2018, identifying associated risk factors, using logistic regression models, and a study of the evolution of rates and the correlation with socioeconomic variables. The analyzes show that the activities developed in certain sectors have a higher risk of resulting in accidents, due to the particularities of each job. The sector of activity that recorded the highest number of accidents was hospital care, specifically nursing technicians and the highest number of deaths was the truck driver profession. The results also indicate that being a man, aged between 34 and 59 years old, widowed, separated or divorced, who is not a business person, has a greater risk of dying as a result of an occupational accident. Also, an accident caused by chemical or physical agents, caused by machines or vehicles, as well as injuries to the head / neck or trunk, has a greater chance of death. No significant correlations were identified with socioeconomic variables, as well as, there was no significant evolution in accident and death rates. It is also worth mentioning the high number of underreporting and underreporting of information, whether it concerns local information, the state of Rio Grande do Sul and Brazil, or international, stressing that this is the main obstacle to obtain reliable statistics. Thus, there is a need to improve official statistics, so that more accurate information is obtained in relation to the situation of accidents and deaths, so that effective measures can be taken not only by the government, but also by employers as a way of mitigate occurrences. Based on the results achieved, it was possible to identify a scenario about the occurrence of accidents and deaths associated with work in Rio Grande do Sul, which can be used to deepen studies in the area, as well as in directing improvement actions in relation to health and safety. occupational, emphasizing the areas and the population that are most vulnerable.